Network pharmacology study on the potential mechanism of Huachansu injection against pancreatic cancer - Lei Xie; Xiang Wang; Xing-yu Chen; Ping-ping Zhai; Xiao Xu; Xiao-tian Shen; Jing-jing Wang (Pharmacological Research - Modern Chinese Medicine)
Introduction: The clinical efficacy of Huachansu in treating pancreatic cancer is well established, the pharmacological mechanism of it has not been fully clarified owing to its intricate composition. Network pharmacology, a novel approach employing bioinformatics, was employed in this study to explore cancer drug targets and interactions. The present research employed network pharmacology and molecular docking techniques to examine the mechanism of Huachansu injection in the treatment of pancreatic cancer. Methods: The compounds present in the Huachansu injection were identified through a comprehensive literature review, while the targets of Huachansu injection were selected from the Swiss Target Prediction database. Genes associated with pancreatic cancer were obtained from the DisGeNET, GeneCards, and OMIM databases. The potential therapeutic targets were determined through Venn diagram analysis. Subsequently, Gene Ontology (GO) enrichment analysis and (Kyoto Encyclopedia of Genes and Genomes) KEGG enrichment analysis were conducted, followed by the construction of a PPI network. Molecular docking was performed using AutoDock Vina. Furthermore, we examined the effects of Huachansu injection on the proliferation and migration of Panc-1 cells using CCK-8 and scratch wound healing assays. Additionally, Western blot analysis was performed to assess the identified core targets (mTOR, HIF-1α). Results: We identified 30 active components and 312 targets of Huachansu injection and 134 potential therapeutic targets of Huachansu injection in pancreatic cancer. Based on the potential therapeutic targets, a complex, multilateral interaction component–target gene network map was constructed. The mechanism by which Huachansu injection combats pancreatic cancer may be related to the signal transduction, cell cycle, immune system and gene expression (transcription). GO analysis showed that therapeutic targets mainly involve protein serine/threonine/tyrosine kinase activity, ATP binding, protein kinase activity, and enzyme binding. KEGG analysis revealed 105 signaling pathways, with PI3K-Akt, HIF-1, and MAPK signaling pathways being the major ones. The main targets of Huachansu injection anti pancreatic cancer were defined via PPI network analysis (STAT3, HIF1A, MTOR, HSP90AA1, ESR1, HSP90AB1, NFKB1, MMP9, AR and CDK2). Among them, STAT3, MTOR, and HIF1A were selected as receptors for molecular docking. The in vitro study found that Huachansu injection can significantly inhibit the viability and migration ability of Panc-1 cells, as well as suppress the expression of mTOR and HIF-1α proteins. Discussion: Huachansu injection has multi-component, multi-target, and multi-pathway characteristics, the potential mechanisms of which in the treatment of pancreatic cancer have been predicted by network pharmacology. Huachansu injection can inhibit the growth and migration of Panc-1 cells, and the suppression of HIF-1 signaling pathway activation may be one of its key mechanisms of action.